The effect of eco-efficiency and good corporate governance on firm value: profitability as a mediator / Enni Savitri and Nik Herda Nik Abdullah - Savitri, Enni; Nik Abdullah, Nik Herda (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
This study examined the value relevance of the “eco-efficiency” concept, which refers to the process of maximizing the effectiveness of business processes while minimizing a company’s environmental impact. The study aimed to determine the effect of eco-efficiency and good corporate governance (GCG) mediated by profitability on enterprise value. A total of 165 firm-years of data from the Indonesia Stock Exchange in the consumer goods industry sector listed from 2016 to 2020 were analysed using ISO certificate implementation criteria. The sampling method used in this study was based on purposive sampling, and the data was analyzed using Partial Least Squares. The results indicated that companies that implement ecoefficiency strategies can boost their firm value. An eco-efficiency strategy can lead to cost reductions and greater profits, which the market must recognize in order to increase profitability. The study also discovered that profitability mediated the relationships between eco-efficiency and firm value. However, it had no effect on GCG’s ability to increase the company’s value. The study’s originality lies in analysing the profitability effect on eco-efficiency, GCG, and firm value at a customer goods company with an ISO certificate 14001.